My American night : poems - Collins, Christopher P., 1974- (University of Georgia Press, 2018)
This collection of lyric poems wrestles with a sense of self that has become fragmented by the experience of war. Christopher P. Collins has taken his tours in the Afghanistan and Iraq wars, extracted their emotional shrapnel, and examined their toll on his civilian life. He considers the two sides of himself that have been wrought in these parallel lives. One is the self of the citizen-soldier, and the other is the self of the husband and father. His poems reveal the brutal ways in which these selves collide and bleed into one another.
Poems.
Keywords: American poetry -- 21st century.; Electronic books.; Livres numériques.; e-books.; American poetry; 2000-2099; poetry.; Poetry; Poetry.; Poésie.